AKIBAT HUKUM WANPRESTASI DALAM PERSPEKTIF KITAB UNDANG-UNDANG HUKUM PERDATA (BW) - Dalimunthe, Dermina (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2017)
In the agreement law, when the debtor is not performing after subpoena, the debtor has defaulted on all legal consequences. In judicial practice, cases of default committed by debtors in general are debtors who do not fulfill the obligation to pay debts / installments to the bank. As a result, the creditor confiscates the collateral and the debtor must pay interest, fees and case fees